The The contribution of large enterprises to the manufacturing industry - implications for Serbia - Djerasimović, Stefan; Savić, Ljubodrag (Industrija, 2025)
This paper aims to examine the structure of manufacturing of selected European countries by enterprise size and compare it with the structure of Serbian manufacturing to better understand the characteristics of Serbia’s manufacturing and provide the answers for the necessary path of future Serbian industrial policy. We used data from Eurostat datasets to calculate the shares of large enterprises in gross value added, employment and exports of selected European countries’ manufacturing. Besides that, we calculated the respective shares in the higher technological level branches of chosen European countries, as well as the labour productivity level of total manufacturing. The same shares and indicators are then calculated for Serbia, using data from the Statistical Office of the Republic of Serbia. The results are similar in both European countries and Serbia. However, having in mind that Serbia’s manufacturing is characterized by the domination of lower technology level branches, it is necessary for Serbia to improve the technological structure of its manufacturing, which will be possible only with the high share of large enterprises in manufacturing production.
Keywords: large enterprises, manufacturing, technological level, industrial policy